Belowground Chemical Interactions: An Insight Into Host-Specific Behavior of Globodera spp. Hatched in Root Exudates From Potato and Its Wild Relative, Solanum sisymbriifolium - Kud, Joanna; Pillai, Syamkumar Sivasankara; Raber, Gabriel; Caplan, Allan; Kuhl, Joseph C.; Xiao, Fangming; Dandurand, Louise-Marie (Frontiers in Plant Science, 2022)
Understanding belowground chemical interactions between plant roots and plant-parasitic nematodes is immensely important for sustainable crop production and soilborne pest management. Due to metabolic diversity and ever-changing dynamics of root exudate composition, the impact of only certain molecules, such as nematode hatching factors, repellents, and attractants, has been examined in detail. Root exudates are a rich source of biologically active compounds which plants use to shape their ecological interactions. However, the impact of these compounds on nematode parasitic behavior is poorly understood. In this study, we specifically address this knowledge gap in two cyst nematodes, Globodera pallida, a potato cyst nematode and the newly described species, Globodera ellingtonae. Globodera pallida is a devastating pest of potato (Solanum tuberosum) worldwide, whereas potato is a host for G. ellingtonae, but its pathogenicity remains to be determined. We compared the behavior of juveniles (J2s) hatched in response to root exudates from a susceptible potato cv. Desirée, a resistant potato cv. Innovator, and an immune trap crop Solanum sisymbriifolium (litchi tomato – a wild potato relative). Root secretions from S. sisymbriifolium greatly reduced the infection rate on a susceptible host for both Globodera spp. Juvenile motility was also significantly influenced in a host-dependent manner. However, reproduction on a susceptible host from juveniles hatched in S. sisymbriifolium root exudates was not affected, nor was the number of encysted eggs from progeny cysts. Transcriptome analysis by using RNAseq revealed the molecular basis of root exudate-mediated modulation of nematode behavior. Differentially expressed genes (DEGs) are grouped into two major categories; genes showing characteristics of effectors; and genes involved in stress responses and xenobiotic metabolism. To our knowledge, this is the first study that shows genome-wide root exudate-specific transcriptional changes in hatched pre-parasitic juveniles of plant-parasitic nematodes. This research provides a better understanding of the correlation between exudates from different plants and their impact on nematode behavior prior to the root invasion and supports the hypothesis that root exudates play an important role in plant-nematode interactions.